Ferrites and ceramic composites : special topic volume with invited peer reviewed papers only - Jotania, Rajshree B.; Virk, Hardev Singh, 1942- (Diffusion and defect data. Solid state phenomena ;, 2013)
The Ferrite term is used to refer to all magnetic oxides containing iron as major metallic component. Ferrites are very attractive materials because they simultaneously show high resistivity and high saturation magnetization, and attract now considerable attention, because of the interesting physics involved. Typical ferrite material possesses excellent chemical stability, high corrosion resistivity, magneto-crystalline anisotropy, magneto-striction, and magneto-optical properties. Ferrites belong to the group of ferrimagnetic oxides, and include rare-earth garnets and ortho-ferrites. Several new hard and soft ferrites, garnets and their composite systems have been developed during recent years, with very large potential applications, which include bio-sensors, targeted drug delivery, magnetic imaging pigments, anti radar coating, microwave components, transparent magnetic plastics, etc. From physical point of view, ferrites present an extremely interesting class of systems with challenging problems. Hence this special volume was prepared with focus on some of these topics of interest to university researchers and entrepreneurs in industry. Scientists and engineers present research and reference papers on the physical, magnetic, and dielectric properties of ferrites, all magnetic oxides containing iron as a major metallic component, and their potential as electromagnetic interference shielding and other commercial applications. The topics include properties and an applications review of yttrium iron garnets, preparing and characterizing nanocomposites for technological applications, modeling the hysteretic behavior of textured and random ferroelectric ceramics, and the effect of heat treatment on microstructures and magnetic properties of strontium hexaferrite nanoparticles prepared in the presence of a non-ionic surfactant.